Ética em pesquisa no Serviço Social: um estudo a partir do Programa de Pós-graduação em Serviço Social e Política Social da Universidade Estadual de Londrina - Sgarbieiro, Márcia (2017)
This thesis aims to analyse the determinations and implications which embrace the demand of research Project submission in Social Service to the Ethics Committee based on the Postgraduate Program on Social Service and Social Politics and of the Ethics Committee in Research with Human Beings of the State University of Londrina. In order to reach this goal, I aim to analyse the ethics grounds built by Social Service and materialized in the Professional Ethics Code of the Social Workers. The needs to develop a study about ethics in Social Service is due to the my insertion to various Ethics Committee in Research during my academic history between 2006 and 2015. To reach the objectives I understand that the researcher must try repeatedly to access the object of study, aiming to get the reality in its multiple determinations. Categories are built every time there is approach and return. These categories allow the evident to make way to wider determinations. The method which is, at the same time, materialistic and dialectic, stems from the empiric and gathers the relation to other empirical groups, its historical origin taking into account the phenomenon historicity and this is rebuilt according to the researcher’s reflection. As method’s categories, those which contemplate the research object were contradiction, historicity, mediation and totallity. My research is exploratory and descriptive, mainly when I locate the Postgraduate Program in Social Service and Social Politics of the State University of Londrina and the Ethics Committee of the same University. This thesis was developed in the chapters. The first delas with my theoretical background based on Barroco (2005). I begin with a discussion about the ethical development aiming the praxis through the Project. The next step is to write about the ethical-political Project historically built by the social workers’ category. I end the first chapter writing about the bioethics and its basis: bioethics principialism.I seek a critique of the bioethical principles based on the Social Service Ethical Code, on Barroco and Terra (2012). I begin the second chapter making history of the developing process of the protocol whose result is the resolution 510/16, which deals with ethics in Human and Social Science research. Still in chapter II, I talk about the research and the production of human knowledge under the historical-critical perspective. I go on the second chapter creating a context and adding caracteristics to my research locus, which is the Postgraduate Program in Social Service and Social Politics of the State University of Londrina. I finish the chapter II positioning the Ethics Committee in Reseach of Human Beings of the State University of Londrina – CEP – UEL. The third chapter deals with my field research. For this section, I interviewed two students and one professor of the program. There are three aspects of my field research: the first is the reasons to submitt or not to the CEP research. Secondly, if there are any problems during the process and why the CEP evaluation process can become a problem through research. Finally, the last aspect relates to the implications of the submission to ethics in Social Service research. I understand that these aspects answer the first question about the implications and determinations of the CEP evaluation about ethics in Social Service research